Training Needs Assessment: The Case of Female Rice Farmers in Northern Iran - Imaneh Goli; Hossein Azadi; Astrida Miceikienė; Vjekoslav Tanaskovik; Ivana Janeska Stamenkovska; Alishir Kurban; Ants-Hannes Viira (Agriculture, 2022)
An appraisal of training requirements responds to the issue of why training is needed and gives some assurance that the services needed to establish and conduct training can achieve the required outcomes based on performance. Therefore, the goal of this study was to examine the educational needs of female rice farmers in Sari (the capital of Mazandaran province located in Northern Iran). This study adopted a descriptive-correlational approach consisting of 1677 female rice farmers in Sari in 2013–2015. Finally, 240 respondents were selected and examined using Cochran’s formula and through stratified sampling with proportional assignment. The results of multivariate stepwise regression indicated that the level of participation (−0.488), the importance of economic factors (0.369), the number of training courses (−0.284), and marital status (−0.179) of female rice farmers were effective on the training needs level. According to the findings, training programs should take into account the educational needs of female rice farmers in order to gain the necessary expertise and skills in new methods and transfer them to other farmers.